Ectopic Prostatic Tissue in Uterine Cervix: A Case Report - Jovanovikj, Rubens; Kostadinova Kunovska, Slavica; Angelovska, Tamara; Krsteska, Blagica; Tanturovski, Dragan; Trajkovikj, Sofija; Spasevska, Liljana (My University, 2022)
Speaking about prostate in the context of a female patient would sound rather odd to the vast majority of interlocutors. We describe a case of ectopic prostatic tissue in the uterine cervix in a 30 years old patient. The microscopic analysis of the cervical cone biopsy showed H-SIL in the lower-left quadrant, diffuse foci of L-SIL, as well as a focus of low-grade cervical glandular intraepithelial neoplasia in the lower-left quadrant. Tubulo-alveolar glands were incorporated deeply in the cervical stroma were identified in the lower right quadrant, lined with two-layered,cuboidal to columnar, secretory epithelium, resting on a basal cell layer. The immunohis- tochemical analysis showed strong and diffuse PSA positivity in the superficial secretory cells, while the basal cells were CKHMW positive, as well as a partial positivity of Smooth muscle actin. Diagnosis of H-SIL accompanied by LCGIN and aberrant prostat- ic glands in the cervical stroma was made. In almost all reported cases, ectopic prostatic tissue in the female genital tract is a benign condition, although a further follow-up of the patients is required. Possible theories of histogenesis include a developmental anoma- ly, metaplasia of pre-existing endocervical glands, and derivation from mesonephric remnants. It is important that pathologists be aware of this condition and to take it into account in the differential diagnosis.
Keywords: Prostatic tissue in uterine cervix; PSA; CKHMW; Immunohistochemistry